Additional risk factors of ventricular repolarization asynchrony in Q-wave myocardial infarction - L. E. Lagunina; E. A. Fedotov; Yu. G. Shwartz (Российский кардиологический журнал, 2007)
The study included 101 patients with acute Q-wave infarction. Standard examination was accompanied by assessment of myocardial repolarization dispersion assessment (Day 1 and Day 7) and Chlamydia pneumoniae and Cytomegalovirus infections. Increased fibrinogen level and Cytomegalovirus infection activity were independent risk factors of ventricular repolarization asynchrony.